(710) Pros and Cons of performance Appraisal - Elhamy, mohamed adel (Institute of National Planning, 1966)
ملخص This research paper provides a comprehensive administrative examination of performance appraisal as a systematic tool for evaluating individual employee performance and future potential within the broader context of their work environment. The author argues that appraisal is not a modern invention but rather an inherent human practice rooted in civilization itself. The study identifies three principal outcomes of appraisal programs: wage structure determination, morale improvement, and management development. Among the sixteen advantages discussed are salary administration, employee counseling, morale building, healthy workplace competition, systematic performance evaluation, training program design, leadership quality enhancement, and support for recruitment and promotion decisions. Conversely, the paper identifies thirteen significant disadvantages, most notably: employee resistance particularly when appraisals focus on personality rather than actual performance; the inherent difficulty of measuring qualitative work contributions; subjective bias arising from supervisor-subordinate personal relationships; managerial resistance to conducting appraisals; ethical concerns regarding the equal worth of human beings; labor union opposition; and systematic rating errors including the halo effect, purpose bias, situational bias, and insufficient evaluator skill. The paper ultimately presents performance appraisal as a double-edged instrument whose effectiveness depends heavily on how objectively and professionally it is designed and implemented. تناولت هذه الورقة البحثية موضوع تقييم الأداء الوظيفي من منظور إداري شامل، إذ استعرض الباحث المفهوم الجوهري لتقييم الأداء بوصفه أداةً منهجيةً تهدف إلى دراسة أداء الفرد وإمكاناته المستقبلية في ضوء سياق عمله الكلي. وقد أوضح الباحث أن تقييم الأداء لم يكن وليد العصر الحديث، بل هو ممارسة متجذرة في طبيعة الإنسان منذ فجر الحضارة. وقد استعرضت الدراسة المخرجات الرئيسية لبرامج تقييم الأداء، والتي تشمل ثلاثة محاور أساسية هي: الهيكل الوظيفي للأجور، وتحسين الروح المعنوية، وبرامج تطوير الإدارة. وفيما يخص المزايا، فقد رصد الباحث ستة عشر فائدةً جوهريةً تشمل: إدارة الرواتب، والإرشاد المهني، وبناء الروح المعنوية، وتعزيز التنافسية بين العاملين، وتقييم الأداء بصورة منتظمة، وتصميم برامج التدريب والتطوير، وتحسين جودة القيادة، فضلاً عن خدمة أغراض التوظيف والاختيار والترقية. في المقابل، كشفت الدراسة عن جملة من السلبيات الجوهرية التي تحدّ من فاعلية هذه البرامج، في مقدمتها: مقاومة الموظفين المُقيَّمين لا سيما حين تنصبّ التقييمات على السمات الشخصية بدلاً من الأداء الفعلي، وصعوبة قياس العمل النوعي غير الكمي، والتحيز الناجم عن طبيعة العلاقة بين الرئيس والمرؤوس، ومقاومة المديرين أنفسهم لعملية التقييم، إضافةً إلى الإشكاليات الأخلاقية المتصلة بمبدأ المساواة بين البشر، ومعارضة النقابات العمالية، والأخطاء المنهجية كأثر الهالة، وضعف مهارات المُقيِّمين.